2014
DOI: 10.5835/jecm.omu.30.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Levels of serum trace elements in ischemic stroke patients

Abstract: Article HistoryReceived 14 / 08 / 2013 Accepted 17 / 09 / 2013The mortality and morbidity of ischemic stroke (IS) can be decreased by early diagnosis and proper treatment of these patients in the emergency department. The levels of trace elements in the human body are important in maintaining the balance in the various biological components. In this study, we examined the impact of imbalance in levels of trace elements in patients with acute IS. In this prospective study, serum copper (Cu), lead (Pb), cadmium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this regard, Gonullu et al Study, demonstrated that stroke and its subgroups associated with some risk factors such as HTN, DM, and also IHD, HLP [28]. Ahangar et al reported that hypertension had significantly associated with hemorrhagic stroke [29].…”
Section: The Role Of Mineral Serum Level In Risk Factor Of Stroke Bamentioning
confidence: 99%
“…In this regard, Gonullu et al Study, demonstrated that stroke and its subgroups associated with some risk factors such as HTN, DM, and also IHD, HLP [28]. Ahangar et al reported that hypertension had significantly associated with hemorrhagic stroke [29].…”
Section: The Role Of Mineral Serum Level In Risk Factor Of Stroke Bamentioning
confidence: 99%